A Mapping Research on Cofiring from 1979 - 2022: Bibliometric Analysis - Muhammad Farras Ilham; Muchammad; Marcelinus Christwardana (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2023)
This study aims to investigate cofiring-themed articles through Bibliometric analysis using Biblioshiny. The metadata comes from the Scopus database, obtained using the keyword "cofiring". Nine hundred twenty-nine documents were obtained over 44 years (1979 – 2022). The study results show that the USA and China are hosts for cofiring researchers. The most relevant author and affiliate is from China, namely Longtu Li from Tsinghua University. The USA is the largest reference country for cofiring research. Cofiring research trends are divided into two clusters: the energy and power generation research cluster and the chemistry and ceramic materials research cluster. In energy and power generation research, three research themes relevant to current and future conditions are related to coal, biomass, and emission. The results of this study provide a comprehensive picture to academics in the fields of energy, power generation, chemistry, and materials science.